Playing the Afterlife: Dante's Otherworlds in the Gaming Age. Issue 7 (29th September 2019) - Rossignoli, Claudia
In the centuries of its continuous circulation, Dante's Comedy has been one the most productive examples of the transmedia potential of literary works. The timeless relevance of its fundamental moral questions, the cosmic dimension of its imaginative power, and the intensity of its realism, all hold unparalleled promise for any kind of adaptation, translation, or transmediation. The Comedy, and especially its first infernal cantica, gets periodically reinvented and transferred into creative outlets that are increasingly technology driven. This article will explore existing gaming adaptations of Dante's Comedy, to focus on the one hand on textual aspects that are mostly exploited to achieve commercial success and on the other on the potential offered by the text and often marginalized by developers. The article will discuss ways in which new creative approaches would allow for a gaming experience with the authenticity, intensity, and relevance of the "original."